[Fol. 05 recto] - Questebrone, Rev John, MA (My University, 1722)
[Former shelf mark Q.5.12] --- Rev Questeborne was domestic chaplain to the Earl of Galway, and vicar of Burnchurch, co Kilkenny, 1716-29. TCD MS 2207 is also by his hand.
A true collection of severall letters on various subjects & c. written by severall persons and on various incidents
The Country about London City out of Blau Atlas by John Questerbone.
Keywords: Plantation records; Cartography; Great Britain -- History -- 18th century; Blaeu's Atlas; London (England); Middlesex (England); Surrey (England); Kent (England); Maps 1720-1730